2014
DOI: 10.4093/dmj.2014.38.2.120
|View full text |Cite|
|
Sign up to set email alerts
|

The Appropriateness of the Length of Insulin Needles Based on Determination of Skin and Subcutaneous Fat Thickness in the Abdomen and Upper Arm in Patients with Type 2 Diabetes

Abstract: BackgroundLonger needle and complicated insulin injection technique such as injecting at a 45-degree angle and making skinfolds may decrease patient compliance to insulin injection therapy. In this light, shorter insulin needles have been recently developed. However, it is necessary to ascertain that such shorter needles are appropriate for Korean patients with diabetes as well.MethodsFirst, the diverse demographic and diabetic features of 156 Korean adults with diabetes were collected by a questionnaire and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
49
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(59 citation statements)
references
References 14 publications
7
49
1
Order By: Relevance
“…Approximately 90% of our patients were obese and had thicker SC fat. We found a significant association between SC thickness of the arm and thigh and BMI, which is consistent with recent studies 24,25 . Therefore, the results could not be extrapolated to patients with normal BMI where the risk for IM injection could be higher.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Approximately 90% of our patients were obese and had thicker SC fat. We found a significant association between SC thickness of the arm and thigh and BMI, which is consistent with recent studies 24,25 . Therefore, the results could not be extrapolated to patients with normal BMI where the risk for IM injection could be higher.…”
Section: Discussionsupporting
confidence: 93%
“…It was found that when patients received injection training from a diabetes nurse, they had a significant decrease in A1C, unexpected hypoglycemia and glucose variability 23 . US of our patients revealed higher mean skin thickness compared to recent studies 24,25 . The mean skin thickness found was less than 2.5 mm compared to 3.1 mm in our study.…”
Section: Discussioncontrasting
confidence: 61%
“…Needles of 5-mm and even 4-mm length are estimated to provide reliable subcutaneous drug delivery, with substantially reduced risk of IM injection. 6,15 This is the first study comparing the PK and GD of insulin after administration of single doses at either a 5-mm or an 8-mm injection depth in both normal weight and obese healthy subjects using the euglycemic clamp procedure. The randomized crossover design was selected to allow comparison between injection depths on an intrasubject basis, allowing each subject to serve as his/her own control.…”
Section: Discussionmentioning
confidence: 99%
“…The skin averages approximately 2-2.5-mm thick and varies in its 95% confidence interval (CI) between 1.25 and 3.25 mm. These studies included patients with type 2 diabetes (T2DM) from the Philippines [9], Korea [10], China [11], and India [12]; both type 1 diabetes (T1DM) and T2DM adults from the USA (including four different ethnic groups) [7]; and children from South Africa [13] and Italy [14].…”
Section: Skin Thicknessmentioning
confidence: 99%